(untitled) (Bangladesh Journal of Agricultural Research, 2007)
The experiments was carried out at the Regional Agricultural Research Station, Ishurdi, Pabna during the growing season 2000-2001 and 2001-2002 to find out suitable planting materials and better management practices for higher yield of pointed gourd. The experiment involved four planting materials viz., straight vine, ring vine, partial tuberous root and mother plant root, and two management practices viz., bamboo pandal and mulch with rice straw. The highest yield of 18.62 t/ha was obtained from mother plant root. The treatment bamboo pandal gave 56% higher yield than the treatment mulch with rice straw. Significantly the highest yield was recorded from mother plant root with bamboo pandal and the lowest was observed in plants grown from partial tuberous root with rice straw mulch. The highest gross return (Tk. 1,58,440 per hectare and net return (Tk. 86,143 per hectare) was obtained from the treatment combination of mother plan root and bamboo pandal. This treatment also showed higher cost of production and BCR (2.19). Bangladesh J. Agril. Res. 32(2) 2007: 247-254.